HUBUNGAN ANTARA KEPEMIMPINAN KEPALA RUANG DENGAN KINERJA PERAWAT DALAM PENERAPAN KESELAMATAN PASIEN DI RUANG RAWAT INAP RUMAH SAKIT - Lidya Maryani (PT.Mantaya Idea Batara, 2022)
Effective leadership is required for decision-safe care. Nurses have a leadership role to play in enhancing patient safety. The head of the room must have good leadership qualities in order to encourage and ensure the execution of an integrated patient safety program. The task of the head of the room is to measure and assess the efficacy of his participation in assisting in the attainment of safety performance so that he may overcome hurdles and inspire others to do their jobs successfully. The goal of this study is to see if there is a link between the leadership of the head of the room and the performance of nurses when it comes to patient safety.A correlational design is used in this study, which employs quantitative research approaches. The participants in this study were nurses who had spent at least one year in the inpatient department of General Hospital in Bandung. Proportional cluster sampling was used to choose the sample, which consisted of 157 nurses. A questionnaire was used to gather data, and the Spearman rank test was used to analyse the results. The findings indicated a substantial association between the ward head's leadership and the nurse's effectiveness in implementing patient safety (r = 0.212, p = 0.008). The more effective the ward head's leadership, the more effective the nurse's performance in implementing patient safety. It is vital to enhance the head of the room's empowering leadership behaviour and to evaluate his or her capacity to implement patient safety goals on a regular basis.